Letter from Max Bredig to Fridel G. Halstead, December 20, 1938 - Bredig, Max Albert (1938)
Max Albert Bredig (1902-1977) writes to Fridel G. Halstead about a misunderstanding regarding obtaining affidavits for his family members.
Keywords: Bredig, Max Albert, 1902-1977; Halstead, Fridel G.; Affidavits